Towards Madrasah Excellence: Shaping a Competitive Culture through Transformational Leadership - Hasmirati, Hasmirati (JURNAL AL-TANZIM, 2025)
This study aims to analyze transformational leadership in shaping institutional performance in higher education that is integrated with spiritual values and local wisdom. The approach used is a qualitative case study, collecting data through interviews, observations, and documentation. Data are analyzed using the Miles and Huberman model thematic analysis technique, which includes data collection, data reduction, and theme arrangement. This process identifies patterns related to transformational leadership, spiritual values, and local wisdom. The analysis results are then used to conclude the influence of these factors on institutional performance. The study's results indicate that applying transformational leadership that integrates cultural and spiritual values can increase the motivation and involvement of lecturers and staff while improving academic performance. This study proves that this approach can encourage increased institutional performance in higher education through five main dimensions: idealized influence, inspirational motivation, intellectual stimulation, individualized consideration, and cultural-spiritual synergy. This study provides implications about the importance of cultural and spiritual contexts in educational leadership practices. Integrating these values creates a harmonious academic environment, strengthens innovation, collaboration, and engagement, and supports the achievement of institutional goals sustainably.